2020
DOI: 10.1155/2020/9815016
|View full text |Cite
|
Sign up to set email alerts
|

Ezetimibe and Improving Cardiovascular Outcomes: Current Evidence and Perspectives

Abstract: Low-density lipoprotein lowering with statins has convincingly and consistently proven to reduce cardiovascular events in both primary and secondary prevention. However, despite high-dose statin therapy, residual cardiovascular risk remains and many patients also do not tolerate statins. Ezetimibe was initially projected as a frontline alternative to statin. It is an intestinal cholesterol absorption inhibitor with modest LDL lowering effects. But, major studies failed to demonstrate any beneficial effect of C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 52 publications
0
12
0
1
Order By: Relevance
“…In addition, cholesterol homeostasis was shown to be regulated by substrate as well. Absorption of cholesterol by the intestine is a major determinant of cholesterol homeostasis and the target of an important cholesterol-lowering drug, ezetimibe (93,94). Furthermore, the cholesterol biosynthesis pathway is essential for homeostasis of the intestinal epithelium (95,96).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, cholesterol homeostasis was shown to be regulated by substrate as well. Absorption of cholesterol by the intestine is a major determinant of cholesterol homeostasis and the target of an important cholesterol-lowering drug, ezetimibe (93,94). Furthermore, the cholesterol biosynthesis pathway is essential for homeostasis of the intestinal epithelium (95,96).…”
Section: Discussionmentioning
confidence: 99%
“…Here we highlighted one example of a pathway that is influenced by substrate with showing the enrichment of cholesterol homeostats in monolayers on Matrigel in comparison to monolayers on collagen. Absorption of cholesterol by the intestine is a major determinant of cholesterol homeostasis and the target of an important cholesterol-lowering drug, ezetimibe (Malhotra, Gill, Saksena, & Alrefai, 2020;Pradhan, Bhandari, & Sethi, 2020). Furthermore, the cholesterol biosynthesis pathway is essential for homeostasis of the intestinal epithelium (McFarlane et al, 2015;Rong, McDonald, & Engelking, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…It is worth mentioning that our study analysed the effects of LLT escalation mostly by adding ezetimibe to high-intensity statins. Although the benefit of ezetimibe has remained uncertain for several years 19 , recent clinical trials have shown that adding ezetimibe to statin therapy elicited a reduction in cardiovascular events and greater coronary plaque regression 16 , 20 , 21 . In this regard, the latest European guidelines raised the recommendation level of ezetimibe in patients who do not achieve LDL-C goal with maximal tolerable dose statins 3 .…”
Section: Discussionmentioning
confidence: 99%